A Comparative Analysis of Constitutional Models for Presidential Term Limit Optimization - Arifin, Firdaus (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The regulation of presidential term limits is a crucial element in maintaining political stability and the quality of democracy in Indonesia, particularly in preventing the concentration of power and authoritarianism. This study aims to analyze and evaluate the ideal model for regulating the presidential term limits in Indonesia, taking into account various comparative approaches from other countries. Using a normative legal research method with a comparative approach, this study examines the strengths and weaknesses of presidential term models in the United States, Germany, and France, and their relevance to Indonesia. The findings suggest that the current limitation of two five-year terms is appropriate for preserving democracy, but there is a need to strengthen oversight and accountability mechanisms. Alternative proposals, such as a single eight-year term, are also evaluated for potential adaptation in Indonesia. The implications of this research underscore the importance of ongoing constitutional reform discussions to further strengthen Indonesia's governance system in maintaining stability and responsiveness to the people's needs.